Population dynamics of the immature stages of Aedes aegypti (Diptera: Culicidae), vector of dengue: a longitudinal study (1996-2000) - Micieli, María V. (2006)
A four year study was conducted on a natural population of immature stages of Aedes aegypti after the re-invasion of Argentina by this vector in 1987. Thirty six plastic containers with 700 ml of dechlorinated water were placed in the La Plata Zoological Garden, La Plata, Argentina. A strip of filter paper around each container was added to facilitate egg counting. Eggs, larvae and pupae were counted weekly in each container from September, 1996 to August, 2000. After egg counting, papers were submerged to facilitate egg hatching and a new paper was placed in each container. Presence of A. aegypti immature stages was recorded from December-January to June during each of the four years of this study. In 1997, 13 105 eggs, 7 978 larvae and 1 476 pupae were registered with 54.7 % positive containers; during 1998, 8 194 eggs, 668 larvae and 142 pupae were recorded with 28.3 % positive containers; 13 510 eggs, 3 690 larvae and 743 pupae were registered during 1999 with 56.7 % positive containers; and 16 327 eggs, 4 669 larvae and 715 pupae during 2000 with 59.3 % of containers with presence of A. aegypti. Egg number and hatching rate were drastically reduced in 1998 when temperatures from December to May were 1 to 2.5 ºC lower than the other years of this study. These colder than usual temperatures in the summer of 1998 were a consequence of the El Niño event.